(3JLQjO GdUMGM GdSJg aj GdMOjKs - (3QRjf Hf eYGhjI Hf YeGQ GdYHOQj GdCfOdSjs
(3ChdgG (B:s
(3GdMeO ddg Cgd GdMeO hhdjg , hGdgGOi Edjg hGdeKjH Hg s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi CKfGA HGH(B" (3dGjSCd Cgd GdTQc Yf GdTgGOI hdG ZjQgG ?? Hbhdg (B: (3hYf CHj gQjQI bGd (B: (3cGf Cgd Gd cJGH jbQChf GdJhQGI HGdYHQGfjI hjaSQhfgG HGdYQHjI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf eMeO Hf Ydi GdeLGgO GdNGUI HJYR s
Keywords: (3GdMOjK h GdeUWdMs